Levantamento sobre as associações e cooperativas de catadores de materiais recicláveis no município de Porto Alegre/RS e avanços na legislação. - Anita Cristina de Jesus; Marc François Richter; Marta Martins Barbosa Prestes (Confins)
The first segment of society to re-signify the concept of "waste" were the waste pickers. Porto Alegre/RS was one of the pioneering municipalities to implement selective collection, integrating these workers into the recycling process. The aim of the article was to carry out a survey of the associations and cooperatives of waste pickers and collectors of recyclable materials that exist in the municipality, listing the advances in legislation. Data on these institutions was obtained from the Municipal Transparency Portal, with data on the number of sorting units (STs); the number of workers; the volume of waste collected and commercialized; the volume of waste and the amounts involved. Selective collection was introduced in the municipality on 7 July 1990, and the first STs were set up from then on. By 2020, sixteen STs had been formalized, with 486 members/cooperators and a volume of materials commercialized in the order of 9,692 tonnes; with the average amount passed on annually by the municipality to each unit in the order of R$67,255.07 (2020 values).